Sustainability Assessment of Certified Tropical Forestry using Emergy Analysis - Izursa, Jose-Luis; Tilley, David R.; Kangas, Patrick (Journal of Environmental Accounting and Management, 2026)
Sustainable forestry production systems, such as certified forestry, re- duced impact logging or sustainable forest management, have become an important part of tropical countries’ strategy to oversee their forest re- sources. Particularly, certification of forest products has become a widely adopted practice as a response to a growing international concern over the ecological and economic sustainability of harvesting natural tropical forests because of the benefits on reducing excessive and unnecessary construction of forest roads, reducing excessive use of heavy machinery, diminishing excessive collateral damage, and improving the inefficient milling processes and wasting of residues. To accomplish the aim of this study, which is to compare conventional and certified forestry we used a systems analysis tool that could integrate various benefits of certified forestry including, stand age, wood harvest, soil losses and economic gain or loss. We found that the affected area under uncertified logging practices is twice the area of certified forestry because conventional prac- tices require more roads, more logging decks and more skid trails. Also, the rate of soil erosion between uncertified logging (154 Mg/ha/yr) and certified logging (66 Mg/ha/yr) is different. Based on these data, we es- timated that the total emergy removed from certified forests was 40% less than the forest under conventional forestry. The fact that certification does a better job of preserving forest while removing wood was also demonstrated through the Environmental Loading Ratio (ELR). We also found that certification leaves forests with a 30% better chance to recover after logging because less wood is removed. But forestry using certifica- tion showed a lower Emergy Yield Ratio (EYR) because the lower yield and the extra cost of certification. Certification is also favored for the higher price for certified wood in international markets. Then, when Bo- livia exports uncertified wood, it obtains a positive benefit, but lower than using uncertified wood domestically (EYR = 20.4). In other words the worst thing the country could do is certify wood for their domestic market and sell uncertified wood abroad.